Becoming Tuteishyi: Ukraine in the New Global Climatic Regime - Ivakhiv, Adrian (East/West, 2024)
This essay draws on earlier research concerning Ukraine’s northwestern borderlands to articulate a conception of the tuteishyi (one who is “from here”) that resonates with the recent experience of Ukrainians who have been defending their homeland—a domain of blue and yellow; of sunflowers and grain fields; and with a history that is very different from that of its imperial-minded neighbour Russia—from invaders who seek to conquer and suppress its distinct Ukrainianness. The tuteishyi has always been place-based and rooted in the ecological realities of landscape and homeland, even if that individual’s identity has historically resisted definitions of national identity. This makes tuteishist' a fluid and ambiguous concept that may be useful in reconsidering identity with respect to a country that is often described as divided between pro-western Ukrainophone “nationalists” and eastern-leaning Russophones. The present article discusses this formulation of the tuteishyi in relation to philosophies of becoming, post-colonial theories of identity, and politico-ecological analyses of Ukraine and of the emerging “global climatic regime.”